The unbearable foreignness of EU law in social policy, a sociological approach to law-making - Barbier, Jean-Claude; Colomb, Fabrice (Paris, 2011)
"The main purpose of the present text is assessing EU law from the perspective of its “impact” on national systems of social protection, social services and labour law: how does EU governance affect “social policy” in the Union? After recalling the main characteristics of EU governance and presenting the relevant actors of the making of EU social law, we systematically compare EU and national law with respect to two essential dimensions: EU law making in general and the special case of “social law”. Eventually we arrive at a global comparative assessment of the respective legitimacies of EU law and national legislation. Considered from the point of view of relevant actors interviewed during the research, the dynamics of this interaction emerges as structurally constrained but rather open-ended."